2014
DOI: 10.1177/2168479013517892
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Pharmacokinetics and Drug Safety Among East Asian Populations

Abstract: Global clinical studies conducted in various countries and regions are increasing. Race and extrinsic ethnic factors are key covariates that may affect the pharmacokinetics (PK), efficacy, and safety of the drug. Genetic similarity among East Asian populations has been confirmed; thus, PK, efficacy, and safety in these populations are expected to be similar, but this has not been confirmed. This study presents a comparison of PK and safety among East Asians from clinical studies sponsored by Pfizer. Four compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…A thorough understanding of regional variations will likely be expected by health authorities (e.g., Pharmaceuticals and Medical Devices Agency) in support of global clinical trial designs and benefit:risk extrapolation not only from the West to Asia but also from the broader Asian region to specific countries and races . Emerging lines of evidence from the genetic, biochemical, and clinical PK levels generally support consistency in clinical pharmacologic characteristics across the Asian races . For example, although the steady‐state exposures of crizotinib are 50% higher in Asian patients compared with non‐Asians, no meaningful differences in exposure or adverse event profile were apparent upon comparison of PK and safety data in Japanese and Korean patients with anaplastic lymphoma kinase‐positive NSCLC .…”
Section: Exposure‐matched Regional Dosing: Globalization In the Settimentioning
confidence: 99%
See 3 more Smart Citations
“…A thorough understanding of regional variations will likely be expected by health authorities (e.g., Pharmaceuticals and Medical Devices Agency) in support of global clinical trial designs and benefit:risk extrapolation not only from the West to Asia but also from the broader Asian region to specific countries and races . Emerging lines of evidence from the genetic, biochemical, and clinical PK levels generally support consistency in clinical pharmacologic characteristics across the Asian races . For example, although the steady‐state exposures of crizotinib are 50% higher in Asian patients compared with non‐Asians, no meaningful differences in exposure or adverse event profile were apparent upon comparison of PK and safety data in Japanese and Korean patients with anaplastic lymphoma kinase‐positive NSCLC .…”
Section: Exposure‐matched Regional Dosing: Globalization In the Settimentioning
confidence: 99%
“…13 Emerging lines of evidence from the genetic, biochemical, and clinical PK levels generally support consistency in clinical pharmacologic characteristics across the Asian races. [29][30][31]72,73 For example, although the steady-state exposures of crizotinib are 50% higher in Asian patients compared with non-Asians, 47 no meaningful differences in exposure or adverse event profile were apparent upon comparison of PK and safety data in Japanese and Korean patients with anaplastic lymphoma kinase-positive NSCLC. 31 Therefore, clinical results from different Asian countries are likely to be broadly useful throughout the region.…”
Section: Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, several studies comparing East Asian populations have indicated no large differences in genetic polymorphisms for major drug‐responsive genes . Further, no clinically relevant differences in PK and safety profiles of 4 compounds with different characteristics, based on analysis of global clinical trial data, have been found . Moreover, the percentage rate of MRCTs for drug development from 2008 to 2015 increased to a higher extent in East Asia than in the USA and Europe .…”
Section: Introductionmentioning
confidence: 99%